High-Throughput Growth of Microscale Gold Bicrystals for Single-Grain-Boundary Studies - Gan, Lucia T (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.